Efficient CO2 Electrocarboxylation Using Dye-Sensitized Photovoltaics - Yingtian Zhang; Huaiyan Ren; Huawei Zhou; Peipei Luo; Qi Wan; Xianxi Zhang; Bo Wang; Baoli Chen; Bo Zhang (Molecules)
This paper presents the solar-driven electrocarboxylation of 2-bromopyridine (2-BP) with CO2 into high-value-added chemicals 2-picolinic acid (2-PA) using dye-sensitized photovoltaics under simulated sunlight. Using three series-connected photovoltaic modules and an Ag electrode with excellent catalytic performance, a Faraday efficiency (FE) of 33.3% is obtained for 2-PA under mild conditions. The experimental results show that photovoltaics-driven systems for electrocarboxylation conversion of CO2 with heterocyclic halide to afford value-added heterocyclic carboxylic acid are feasible and effective.